Building capacity for testing sterile insect technique against Aedes-borne diseases in the Pacific: a training workshop and launch of sterile insect technique trials against Aedes aegypti and arboviral diseases - Nicole Foley; Florence Fouque; Qingxia Zhong; Herve Bossin; Jeremy Bouyer; Raman Velayudhan; Randall Nett; Anna Drexler (BMC, 2024)
Abstract Background Vector-borne diseases cause morbidity and mortality globally. However, some areas are more impacted than others, especially with climate change. Controlling vectors remains the primary means to prevent these diseases, but new, more effective tools are needed. The World Health Organization (WHO) prioritized evaluating novel control methods, such as sterile insect technique (SIT) for control of Aedes-borne diseases. In response, a multiagency partnership between the U.S. Centers for Disease Control and Prevention (CDC), the Special Programme for Research and Training in Tropical Diseases (TDR), WHO, and the International Atomic Energy Agency (IAEA) supported the operational implementation and evaluation of SIT against Aedes aegypti and arboviral diseases in the Pacific through a consortium of regional partners (PAC-SIT Consortium). Main text A workshop was held from 2 to 6 May 2023, during which PAC-SIT country participants, researchers, and stakeholders in SIT, scientific advisory committee members, and organizational partners came together to review the principles and components of SIT, share experiences, visit field sites and the SIT facility, and officially launch the PAC-SIT project. Working in groups focused on entomology, epidemiology, and community engagement, participants addressed challenges, priorities, and needs for SIT implementation. Conclusions The PAC-SIT workshop brought together researchers and stakeholders engaged in evaluating SIT for arboviral diseases in the Pacific region and globally. This training workshop highlighted that many countries are actively engaged in building operational capacities and phased testing of SIT. The workshop identified a key need for robust larger-scale studies tied with epidemiological endpoints to provide evidence for the scalability and impact on mosquito-borne diseases.